PENGARUH DISIPLIN DAN KEPRIBADIAN PEGAWAI TERHADAP KINERJA PEGAWAI RUMAH SAKIT ISLAM SITI KHADIJAH PALEMBANG - Deasy Idariany (Universitas Prof. Dr. Hazairin SH, 2018)
This research aim to know Influence of Personality and Dicipline and Dicipline toward Official Performance at Siti Khadijah Hospital’s Palembang. Raised hypothesis (1) Anticipated there are positive and significant influence of Personality toward Official Performance at Siti Khadijah Hospital’s Palembang (2) Anticipated there are positive and significant influence of Dicipline toward Official Performance at Siti Khadijah Hospital’s Palembang (3) Anticipated there are positive and significant influence of Personality and Dicipline toward Official Performance at Siti Khadijah Hospital’s Palembang. This research population is officer at Siti Khadijah Hospital’s Palembang amounting 426 people, sample taken 85 people divice while test drive instrument sample taken 30 people and research sample taken 55 people. Data collected by questionare distribution. This research used descriptive statistic analysis and inferential statistic. The data processing used SPSS Program, 12.0 released. Based on t-test at first hypotesis, t-counting 6,437 with significant degree 0,000 less than 0,05, that Personality positive and siginficant influence toward Official Performance. Second hypotesis, t-counting 7,760 with significant degree 0,000 less than 0,05, that Dicipline positive and siginficant influence toward Official Performance.While third hypotesis,F-test, F-counting 30,385 with significant degree 0,000 less than 0,05, there are positive and siginficant influence of Personality and Dicipline toward Official Performance at Siti Khadijah Hospital’s Palembang. Result of analysis data there are correlation (R) between Personality and Official Performance are 0,662 and coefficient determination (R-sequare) 0,439. Correlation (R) value between Dicipline and Official Performance are 0,729 and coefficient determination (R-sequare) 0,532. Multiple correlation between Personality and Dicipline by simultan 0,734 and coefficient determination (R-sequare) 0,539. R-sequare 0, 539, meaning that 53,90% Official Performance at Siti Khadijah Hospital’s Palembang can be explained by variable personality dan employee dicipline, the rest (46,10%) explained or influenced by another factors like leadership, competency, motivation, and facilities. Double regression egurva was : Ŷ = 12,526 + 0,210X1 + 0,580X2 + e.